Hepatitis B Virus Nucleocapsids Formed by Carboxy-Terminally Mutated Core Proteins Contain Spliced Viral Genomes but Lack Full-Size DNA - Köck, Josef (American Society for Microbiology, 2004)
The carboxy-terminal sequence of the hepatitis B virus (HBV) core protein constitutes a nucleic acid binding domain that is rich in arginine residues and contains three serine phosphorylation sites. While dispensable for capsid assembly, this domain is involved in viral replication, as demonstrated by the effects of mutations on RNA packaging and/or reverse transcription; however, the underlying mechanisms are poorly understood. Here we tested a series of core protein mutants in which the three serine phosphorylation sites were replaced by glutamic acid, in parallel with a previously described deletion variant lacking the 19 C-terminal amino acid residues, for their ability to support viral replication in transfected hepatoma cells. Replacement of all serines and the deletion gave rise to nucleocapsids containing a smaller than wild-type DNA genome. Rather than a single-stranded DNA intermediate, as previously thought, this was a 2.0-kbp double-stranded DNA molecule derived from spliced pregenomic RNA (pgRNA). Interestingly, full-length pgRNA was associated with nucleocapsids but was found to be sensitive to nuclease digestion, while encapsidated spliced RNA and 3′ truncated RNA species were nuclease resistant. These findings suggest that HBV pgRNA encapsidation is directional and that a packaging limit is determined by the C-terminal portion of the core protein.